Study on energy separation characteristics inside the vortex tube at high operating pressure. (December 2019) - Liang, Fachun; Wang, Huazhong; Wu, Xueying
Highlights: A 3D CFD model using real gas equation has been developed. Temperature separation characteristics at high operating pressure are investigated. The difference between high and low operating pressure are compared. Effect of inlet pressure and geometrical size are examined. Abstract: Although the flow and heat transfer process inside the vortex tube at low operating pressure were studied intensively, little attention has been devoted to the energy separation characteristic at high operating pressure. In present work, a 3D numerical model has been developed to investigate the difference of flow and heat transfer characteristics of a vortex tube between low-pressure and high-pressure system. The working fluid is methane and real gas model is applied for physical properties calculation. The pressure, temperature and velocity distribution characteristics of low operating pressure and high operating pressure are obtained and compared. The cold and hot temperature differences, the coefficient of performance are applied to evaluate the effect of inlet pressure and geometrical size on the performance at high pressure condition. It is interesting to find that much lower temperature distribution is obtained at high operating pressure and the hot exit temperature may be even lower than that of inlet. In case of same inlet-outlet pressure ratio, larger vortex size lead to higher cold temperature difference but vortex tube size has little influence on hot temperature difference as well as the coefficient of performance.